Profiling causative factors leading to construction project delays in the United Arab Emirates - Mpofu, Bekithemba; Ochieng, Edward Godfrey; Moobela, Cletus; Pretorius, Adriaan (Emerald, 2017)
Purpose A voluminous amount of research has been conducted on project delay in the recent past; however, the persistence of the problem demands that a relentless quest for solutions is upheld. It can be argued that the problem is likely to be more pronounced in areas where development pressure is the highest. One such area is the United Arab Emirates (UAE) where the construction industry is said to have reached an unparalleled position in the last decade. The purpose of this paper is to identify the most significant causes of delays in the UAE construction industry. Design/methodology/approach A survey was conducted targeting three key types of stakeholders, namely clients, contractors and consultants. Validity and reliability were achieved by first assessing the plausibility of construction delay variables in UAE. The verification took place after the interpretation of quantitative data, this involved presenting the findings to the main participants. The validation took place after the verification process. Rigour was achieved by engaging participants previously engaged in UAE and focussing on verification and validation, this included responsiveness of the researchers during group discussions, methodological coherence, appropriate sampling frame and data analysis. Findings From the analysis, the study unveiled a number of important causes of construction delays in the UAE, ranging from unrealistic contract durations to poor labour productivity, with consultants and clients seemingly shouldering the bulk of the “blame game”. It was evident that all the three main stakeholders in a construction project (clients, consultants and contractors) need to change their existing practices in order to ensure timely delivery of projects. The research also confirms that delays are country specific and appear to be time related hence they should be viewed within the social, economic and cultural settings of the UAE. Research limitations/implications A major limitation of the current study was the use of a single approach to facilitate data collection. Practical implications It was evident that practitioners need to change their existing practices in order to ensure timely delivery of projects. Continuous coordination and relationship between practitioners are required through the project life cycle in order to solve problems and develop project performance. Originality/value As suggested in this study methods should be put in place to reduce long and bureaucratic processes within the client’s organisations, not only to fulfil the requirements of the contract but also to suite fast-track projects.
Keywords: Project management; United Arab Emirates; Construction industry; Construction delay; Construction practitioners; Delivery of projects